Peoples Interest, The Neglected Feature of The Reformasi. The Case of Indonesian Defense Diplomacy - Harsawaskita, Adrianus (Jurnal Ilmiah Hubungan Internasional, 2015)
Law of the Republic of Indonesia on the State Defense stipulates among others: the active role of the Army in maintaining regional and international peace, defense diplomacy, as well as incorporating people and other resources in defending the country. The inauspicious Indonesian defense diplomacy towards Singapore in the form of Defense Cooperation Agreement (DCA) of 2007 planned to beef up both military cooperation and mutual confidence. The planned joint training would exploit not only Indonesian territories, but also affect peopleâs livelihood and safety. Utilizing people in the implementation exposes loopholes in the regulation(s) of the state defense. Should government consult the concerned people? Indeed, people were not consulted as the existing regulations sidestep people in the process to reach an agreement in DCA. And that is one of the case of neglecting people interest in the reformasi era.Â